OSTEOMYELITIS AFTER OSTEOSYNTHESIS USING OF METAL IN PATIENTS WITH CLOSED FRACTURES OF TUBULAR BONES - R. A. Kryuchkov; M. S. Kunafin; S. N. Khunafin (Креативная хирургия и онкология)
In connection with  the  expansion of  indications for  osteosynthesis with  the  use  of metal,  the  surgical  treatment of  closed  fractures of  the  bones, increases  the  frequency of postoperative osteomyelitis. We analyzed  the results of treatment of 102 patients with postoperative osteomyelitis treated at City Clinical Hospital number 18 in 2008-2011.We  investigated laboratory parameters  (levels  of  procalcitonin, C-reactive  protein and leukocyte  index of intoxication) in 25 patients undergoing osteosynthesis using metal structures in closed fractures of tubular bones.  After osteosynthesis using metal structures in closed fractures of tubular bones in 3,2% of  cases  developed  postoperative  osteomyelitis.  The  changes  in  laboratory  parameters  in 16 (64%) patients, in other  cases  results  were  within normal  limits. Study of the  levels of procalcitonin, C-reactive protein and leukocyte index of intoxication do not have significant practical value for predicting postoperative osteomyelitis.